2022
DOI: 10.1177/0271678x221083387
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning based analysis of stroke lesions on mouse tissue sections

Abstract: An unbiased, automated and reliable method for analysis of brain lesions in tissue after ischemic stroke is missing. Manual infarct volumetry or by threshold-based semi-automated approaches is laborious, and biased to human error or biased by many false -positive and -negative data, respectively. Thereby, we developed a novel machine learning, atlas-based method for fully automated stroke analysis in mouse brain slices stained with 2% Triphenyltetrazolium-chloride (2% TTC), named “StrokeAnalyst”, which runs on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Like other studies combing machine learning and disease models, 27,55 it is hoped the findings of this study would be valuable for…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Like other studies combing machine learning and disease models, 27,55 it is hoped the findings of this study would be valuable for…”
Section: Discussionmentioning
confidence: 89%
“…Like other studies combing machine learning and disease models, 27,55 it is hoped the findings of this study would be valuable for clinical practice and to improve patient outcomes. A key point making future translational research promising is that the optimal algorithms and predictive models showed good and stable performance in other external datasets.…”
Section: Discussionmentioning
confidence: 91%
“…Recognizing the pitfalls of missing data, we employed advanced imputation techniques grounded in probabilistic frameworks to ensure coherent value replacement [ 24 ]. Outliers, which can jeopardize model accuracy, were identified and rectified using robust statistical methodologies such as the IQR method and Z-score method [ 25 , 26 , 27 , 28 , 29 , 30 ]. Furthermore, given the sensitivity of machine learning algorithms to feature scales, normalization processes like Min–Max scaling and Z-score normalization were utilized, ensuring consistent interpretability and optimization across all variables [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%